The Thermonuclear X-Ray Bursts of 4U 1730-22 - Bult, Peter (2022)
We present observations of the historic transient 4U 1730-22 as observed with the Neutron Star Interior Composition Explorer (NICER). After remaining in quiescence since its 1972 discovery, this X-ray binary showed renewed outburst activity in 2021 and 2022. We observed 4U 173-22 extensively with NICER, detecting a total of 17 thermonuclear X-ray bursts. From a spectroscopic analysis, we find that these X-ray bursts can be divided into a group of bright and weak bursts. All bright bursts showed 1-2 s rise times and a photospheric radius expansion phase, while the weak bursts showed a slower ∼5 s rise with a tendency for concave shapes. From the photospheric radius expansion flux, we estimate the source distance at 6.9 ± 0.2 kpc. We consider various interpretations for our observations and suggest that they may be explained if accreted material is burning stably at the stellar equator and unstable ignition occurs at a range of higher latitudes.